Eksplorasi Cemaran Mikroba Staphylococcus aureus dan Perhitungan Total Plate Count Pada Daging Ayam Broiler Dari Pasar Modern di Kota Surabaya - Arsa Thalita Jazinda Putri; Isnawati Isnawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Broiler chicken meat is a widely consumed animal protein source; however, it is highly susceptible to microbial contamination that can compromise food quality and safety. Contamination of Staphylococcus aureus in animal-derived food products serves as a critical indicator of hygiene and sanitation practices and poses risks of various health disorders. Objective: This study aimed to determine the microbial contamination levels of Staphylococcus aureus and the Total Plate Count (TPC) values in broiler chicken meat obtained from several modern markets in Surabaya City, as well as to evaluate its safety level based on SNI 9159:2023 concerning Microbiological Criteria for Animal-Derived Food Products. Methods: This study employed a descriptive exploratory method with 10 broiler chicken carcass samples purposively collected from two different modern markets in Surabaya City. S. aureus testing was conducted using the spread plate method on Baird-Parker Agar media, followed by coagulase test and Gram staining for specific confirmation, while TPC testing utilized the pour plate method on Plate Count Agar media. Results: The results showed that 3 out of 10 samples were detected to contain S. aureus with contamination values ranging from 2.6 × 10⁴ CFU/g to 3.0 × 10⁴ CFU/g, which exceeded the maximum limit of SNI requirement of 1 × 10⁴ CFU/g. All samples exhibited TPC values ranging from 1.5 × 10⁴ to 3.5 × 10⁴ CFU/g, which remained below the maximum SNI limit of 1 × 10⁶ CFU/g. Conclusion: Some broiler chicken meat samples from modern markets in Surabaya City remained contaminated with S. aureus above the permissible threshold, necessitating attention to handling practices, sanitation, and storage conditions. Chicken meat should be cooked at high temperatures and consumed in well-done condition to ensure food safety for public health.